Unburnable carbon in the rapidly warming Arctic: Mapping spatial relationships among oil and gas development, ecologically sensitive areas and Indigenous Peoples’ lands - Daniele Codato; Daniele Vezzelli; Federica Ammaturo; Giorgia Lazazzera; Andrea Stralla; Salvatore E. Pappalardo; Massimo De Marchi (PLoS ONE, 2026)
As global temperatures rise due to carbon emissions from fossil fuels, it is estimated that around 60% of oil and gas reserves —termed 'unburnable carbon'—must remain underground to meet international climate targets. The Arctic, warming nearly four times faster than the global average, is a frontline for both climate change impacts and oil and gas development, which pose severe risks to its fragile biodiversity and Indigenous communities. This study presents the first comprehensive spatial atlas of Arctic oil and gas infrastructure using open-access data, assessing overlaps with ecologically sensitive areas and Indigenous Peoples’ lands (IPLs) within the Conservation of Arctic Flora and Fauna (CAFF) boundary. The analysis identified 512,306 km 2 of exploited territory (1.82% of the Arctic region), 44,539 wells, 39,535 km of pipelines, and over 1.95 million km of seismic lines. Results show that 73.30% of hydrocarbon areas intersect IPLs and 7.57% overlap protected areas, with developments located in close proximity to key ecologically sensitive areas and culturally significant sites. These findings highlight the spatial overlaps and potential tensions between oil and gas industry interests and those behind the geographies of ecologically sensitive areas and IPLs, especially in zones such as Alaska’s North Slope and Russia’s Yamal Peninsula. The study calls for a paradigm shift in Arctic governance, from resource extraction toward equity, ecological preservation, and Indigenous inclusion. It supports the implementation of Arctic-specific supply-side climate policies, such as establishing an Arctic Fossil Fuel Non-Proliferation zone, to prevent further ecological degradation and to ensure a just transition. By integrating spatial justice criteria into decision-making, this work provides a tool for guiding sustainable and inclusive land-use and energy transition planning across the region.